Studies on pulling force as drought resistance screening method and genetics of upland rice root characteristics. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1986)
ABSTRAK The main objective of this research is to develop pulling-force technique as an easy and simple drought resistance screening method for a large number of breeding lines in a relatively short period. For this purpose, field experiments were conducted by planting several varieties and lines representing different degrees of drought resistance, i. e. MI 48, IR 1750 F5 B-5, C 22, IR 20, IR 26, IR 442-2-58, Salumpikit, 0S4 and MGL 2_ during the rainy season of 1976/1977 at Los Banos, Philippines and the rainy and dry seasons of 1980 and 1981 at Yogyakarta, Indonesia. Studies were made of on the relationship between pulling-force and drought resistance scale according to the IRRI standard evaluation system for rice, correlation between pulling-force and root characteristics, path coefficients of root characteristics to pulling-force and the determination of the appropriate time (age) of pulling-force and root characteristics measurement. Similar experiments and pot experiments using regosol and grumusol soil were also conducted to study the environmental effects on the pulling-force and root growth. Pulling force technique evaluation was carried out by regressing drought resistance scale on pulling-force measurement using F4 and F5 breeding fines derived from crossings of the varieties mentioned, planted in the 1981 and 1982 rainy season and in the 1982 and 1983 dry season. The Fl and F2 generation of the crosses were used for studying the genetics of root characteristics. The following are the results of the experiments. There was a significant correlation between pulling-force and drought resistance scale, the heavier the drought stress the closer the relationship. Pulling-force was directly and positively affected by the thick root number, but directly and negatively affected by the total root number. It means that thick root number should be strongly considered in drought resistance breeding. Broad sense heritabilities of root characteristics increased hyperbolically with the age of plant, and became practically constant at the initiation of flower primordia. This suggests that the appropriate lime of pulling-force and root characteristics measurements should be carried out at this growth stage. Pulling-force and root characteristics were affected by the root growth environment. The non significant genotype s environmental interaction indicates that the rank of cultivars for pulling-force and root characteristics are constant over a wide range of environment. The regression of drought resistance scale on pulling-force was not significant for F4 and F5 segregating breeding lines, eventhough the relationship tended to increase. Total root number, thick root number, maximum root length and total root weight are quantitative characters, governed by polygene, varied from no dominance, partial dominance and over dominance depending on the type of parental crosses. The values of the broad sense heritability of these root characteristics ranged from 0.39 (medium) to 0.91 (high) depending also on the type of parental crosses. From the results of these studies the following conclusions can be made. Key words: teknik gaya cabut,, metode penyaringan